Renal drug dosing practices and clinical outcomes in patients with kidney disease admitted at two referral hospitals in Northwest Ethiopia - Gebeyaw Addis Bezie; Meseret Adugna; Gizachew Tadesse Wassie (BMC Nephrology)
Abstract Background Kidney disease; including acute kidney injury (AKI) and chronic kidney disease (CKD) is a significant global health burden, contributing to cardiovascular and cerebrovascular morbidity and mortality. Patients with any degree of renal disease are at risk of drug metabolism and excretory function loss. Toxicity from lack of proper drug or metabolite excretion and ineffective dosing from renal adjustment likely affects the clinical outcome of critical patients among other factors. In Ethiopia, predictors of poor outcomes related to dose adjustments remain understudied, causing uncertainty in clinical dosing practices. This study aimed to assess renal drug dose adjustment practice and patient outcomes in hospitalized patients with kidney diseases. Methods An institution-based, Cross-sectional study was conducted from December, 01/2023- February, 29/2024. A total of 403 patients were selected using a systematic random sampling technique. A pre-tested semi-structured questionnaire was used to collect data which was entered to Epi data version 3.1 and exported to SPSS for analysis. Descriptive statistics were used to summarize socio-demographic and clinical data, as well as the proportions of patients with poor treatment outcomes and the proportions that received different levels of renal drug dosage adjustment services. Bivariable and multivariable logistic regression analyses were employed to estimate the crude and adjusted odds ratio with a confidence interval of 95% and a P value of less than 0.05 considered statistically significant of predictors with patients treatment outcome. Results Among the 384 patients with renal disease, more than one-third (36.5%), 95%CI (31.8%-41.3%) had poor treatment outcomes. The practice of renal drug dose adjustment was poor; revealing only 23.2% compliance with dosing guidelines. Partial renal drug dose adjustment (AOR= 2.76, 95% CI:1.14-6.71), no renal drug dose adjustments (AOR= 10.15, 95% CI: 3.88-26.57), mechanical ventilator use (AOR=2.90, 95% CI:1.69-12.19), vasopressor use (AOR=10.01, 95% CI: 4.27-22.73), presence of comorbidity(AOR=3.42, 95% CI:1.56-7.51), advanced stage of AKI: stage II (AOR= 2.51, 95% CI:1.15-5.45) and stage III (AOR=2.92, 95%CI: 1.29-6.57), intrinsic type of AKI(AOR=3.56, 95%CI:1.57-8.06) and age above 60 years(AOR=5.50, 95%CI: 2.26-13.41) were associated with poor patient outcome defined by development of complications, need for dialysis or death. Conclusions This study revealed that there is a significant level of poor patient outcomes in hospitalized patients with renal failure. Patients receiving partial or no drug dose adjustments were associated with significantly poorer clinical outcomes along with other factors including old age, presence of comorbidities, severity and type of AKI. Therefore, we recommend a holistic approach in the care of renal patients and prompt consideration of adherence to guidelines in drug dosing. Trial registration Was not applicable because the study was not clinical trial.